The analysis of studentsâ learning outcomes who graduated from natural science and social science at accounting education study program, The economics faculty, universitas negeri makassar - Sahade, Sahade; Ngampo, M. Yusuf A. (Dinamika Pendidikan, 2016)
The objective of the study was to determine the differences of studentsâ learning outcomes who graduated from natural and social sciences at Accounting Education Study Program in the Faculty of Economics, Makassar State University. The variable of this study was studentsâ learning outcomes who graduated from natural and social sciences at Accounting Education Program. The population of the study were students of Accounting Education Study Program in the year of 2011 until 2012 and the samples of the research were 50 undergraduate students who graduated from natural science, and 50 undergraduate students who graduated from social science. It used purposive sampling to get the samples with the certain criteria. The data were collected through questionnaires and the data on studentsâ study backgrounds were taken from simpadu. Then, the data were analyzed by descriptive statistical analysis. Based on the results of questionnaires and analysis, it showed that the averages of studentsâ learning outcomes on both Introduction to Accounting 1 and Introduction to Accounting 2 Subjects were 2.89 for students who graduated from natural science and 2.81 for students who graduated from social science. Then; studentsâ learning outcomes who graduated from natural science on Introduction to Accounting 1 subject was 2.80 and 2.98 for Introduction to Accounting 2. Whereas; studentsâ learning outcomes who graduated from social science for Introduction to Accounting 1 was 2.95 and Introduction to Accounting 2 was only 2.68. It can be concluded that studentsâ learning outcomes on Introduction to Accounting 1 and Introduction to Accounting 2 who graduated from Social science got the lower scores than students who graduated from natural science. It happened because the learning method which was used by Natural science graduates was more practical and Â the Social science graduates usually had more discussions because they thought they already had the basic knowledge of accounting.